Electrochemical transformation of black phosphorous to phosphorene quantum dots: effect of nitrogen doping. (4th February 2020) - Ozhukil Valappil, Manila; S, Jamal Mohamed; Alwarappan, Subbiah; Pillai, Vijayamohanan K
Abstract: We present a comparative analysis of the structural and optical properties of electrosynthesized PQDs, a new class of size-tunable luminescent materials and their nitrogen doped counter parts(NPQDs). Nitrogen doping onto phopshorene lattice could be realized i n situ at room temperature using either nitrogen containing electrolyte and/or supporting electrolyte in the solution. An increased quantum efficiency as well as redox behavior has been observed for PQDs upon nitrogen doping and a critical analysis of the effect of nitrogen on the structural, optical and electrochemical properties of PQDs suggests several potential benefits of applications ranging from electrocatalysts and molecular electronics to different types of sensors and bioimaging.